Potential Role of HPA Axis and Sympathetic Nervous Responses in Depletion of B Cells Induced by H9N2 Avian Influenza Virus Infection - Qi, Wenbao (Public Library of Science, 2012)
Except severe pulmonary disease caused by influenza virus infection, an impaired immune system is also a clinic characteristic. However, the mechanism(s) of influenza virus infection-induced depletion of B cells was unknown. Here, we compared the effect of two variant virulence H9N2 virus infections on mouse B cells. Our study found that the infection with highly pathogenic virus (V) of led to depletion of spleen B cells and bone marrow (BM) early B cells, compared to lowly pathogenic virus (Ts). Moreover, high apoptosis and cell cycle arrest in spleen and BM were detected, suggesting important factors for the reduction of B cells in both organs. Further, this effect was not caused by virus replication in spleen and BM. Compared to Ts virus infection, V virus resulted in higher glucocorticoids (GCs) and lower leptin level in plasma. Intraperitoneal GCs receptor antagonist RU486 injection was sufficient to prevent the loss of spleen B cell and BM pro- and immature B cells, but similar result was not observed in leptin-treated mice. Depletion of spleen B cells and BM pro-B cells was also reversed by chemical sympathectomy mediated by the norepinephrine (NE) analog 6-hydroxydopamine (6-OHDA), but the treatment didn't affect the GCs level. This study demonstrated that depletion of B cells induced by H9N2 AIV was dependent on HPA axis and sympathetic response.